Methylation of glutathione S-transferase pi 1 as an epigenetic biomarker for prostate cancer detection in black South African men - Hayes, Vanessa M. (University of Pretoria, 2022)
Dissertation (MSc (Human Genetics))--University of Pretoria, 2021.